2022
DOI: 10.1186/s12912-022-01149-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep quality among nurse managers during regular prevention and control of the COVID-19 in China: a cross-sectional study

Abstract: Background Nurse managers play a pivotal role in quality patient care and staff satisfaction and retention. An overwhelming amount of work tasks and responsibilities might result in their sleep problems which are expected to aggravate in the context of the COVID-19, thereby affecting their overall health and work quality. However, little attention has been paid to sleep quality among nurse managers. This study aimed to investigate the prevalence of sleep disorders among nurse managers and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…This might be due to the stress-reducing effects of exercise, which in turn could improve sleep quality. This observation is consistent with the studies by Strand et al (2013) and Chen et al (2022) , which noted that the frequency of exercise positively influenced the sleep quality of nurses.…”
Section: Discussionsupporting
confidence: 93%
“…This might be due to the stress-reducing effects of exercise, which in turn could improve sleep quality. This observation is consistent with the studies by Strand et al (2013) and Chen et al (2022) , which noted that the frequency of exercise positively influenced the sleep quality of nurses.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that regardless of their place of work, healthcare workers, mainly female nurses, experienced symptoms of anxiety and stress, which resulted in decreased sleep and quality of life [ 18 ]. Consistent with a previous study, we found that the front-line nurses were associated with severe sleep difficulty as they have a high risk of infection due to their heavy workload and long working hours [ 19 ]. A study clearly demonstrated high rates of stress, anxiety, and depression among front-line healthcare workers caring for COVID-19 patients [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…This nding is consistent with prior research that patients underwent the transplantation of hematopoietic stem cells experiencing signi cant sleep disturbances (23). It is noteworthy that sleep quality is in uenced by various external factors, such as environmental conditions, psychological diseases and lifestyle choices (24), which may impact the response to HUC-MSC infusion in the context of sleep quality. Also, a longer follow-up period may provide a more comprehensive understanding of MSC therapy on sleep quality.…”
Section: Discussionsupporting
confidence: 89%